The Country of Origin and the Consumer Behavior - How to Improve Chinese Products Brands? - Kerbouche, Mohammed; Adouka, Lakhdar; Belmimoun, Abdenour; Guenouni, Habib (Mediterranean Journal of Social Sciences, 2012)
There are two objectives of the project. First is to assess the overall image of China brand products in consumers’ minds. Countries of origin effect influences people’s evaluations on products and purchase decisions since people have different perceptions towards different countries and products. This is because each country has its own political, technological and economical environment. In consumers’ minds, they have negative attitudes on China brand products, such as old-fashioned, cheap, etc. So, there is negative country of origin effect on China brand products in markets. This is the first reason for doing this project. Second objective is to analyze the data for our survey and give some suggestions and recommendations. We choose a specific product electric for our Study and we made some comparison between Chinese brand Lenovo and the Japanese brand Sony, I chose this two brand as Lenovo one of the most famous brand in China, and Sony as one of the big electronic company in the world. Consumers’ attitude towards electric appliance may influence their purchase of the products, which are in China or foreign brands. Besides, consumers’ attitude towards brand image may also affect their purchase decision among different brands of products. There are some factors help constructing consumers’ attitudes towards brand image, such as advertising, quality, price, technology and package. Moreover, other variables, such as sex, age, income and educational level can also influence consumers’ purchase decisions among different brand products. On the other hand, this study mainly focuses in 19 countries.